Generation Z: Understanding the Moral Characteristics of The Current Generation - Harmelia Tulak; Alexander Pakiding; Topanus Tulak; Asri Pongsirante (Edumaspul: Jurnal Pendidikan, 2023)
Generation Z, which is currently dominated by students and college students, is a generation that has experienced growth in line with technological advances. The large number of media interventions and easy access to detrimental information can hinder efforts to instill positive moral values. One of the first steps in designing and developing moral learning strategies that suit students' needs is to understand their moral characteristics. Therefore, the aim of this research is to reveal the characteristics of Generation Z in terms of their moral considerations. This research involved 63 generation Z students and used descriptive methods, with data collection carried out through a test technique known as the "moral reasoning test". The research results indicate that the moral development of generation Z students tends to be at a conventional level, dominated by stage 4 followed by stage 3. In this stage, good actions are carried out by obeying obligations and respecting authority. This reflects social conformity, where individuals tend to act in accordance with social norms to gain positive recognition from friends or other adults.